Resposta :
a) 4x²-3x+3-2x²-3+7x = 2x²+4x
b) 15y³+5y²+y-1-8y³+8y²+5y+3 = 7y³+13y²+6y+2
c) (x²+3x-1) + (9x²-12x-9) = 10x²-9x-10
d) (4x³-4x²+2x+1) – (2x³-3x²+x+2) =
4x³-2x³-4x²+3x²+2x-x+1-2
2x³-x²+x-1
❤️ Boa noite ❤️
05/08
![Ver imagem GLAUCIACKLESSPAA44T](https://pt-static.z-dn.net/files/d8b/3df8495e58137b61521e57ef250444c5.jpg)
a) 4x²-3x+3-2x²-3+7x = 2x²+4x
b) 15y³+5y²+y-1-8y³+8y²+5y+3 = 7y³+13y²+6y+2
c) (x²+3x-1) + (9x²-12x-9) = 10x²-9x-10
d) (4x³-4x²+2x+1) – (2x³-3x²+x+2) =
4x³-2x³-4x²+3x²+2x-x+1-2
2x³-x²+x-1
05/08